An in situ investigation of the water-induced phase transformation of UTSA-74 to MOF-74(Zn). Issue 29 (24th February 2017) - Bueken, Bart; Reinsch, Helge; Heidenreich, Niclas; Vandekerkhove, Annelies; Vermoortele, Frederik; Kirschhock, Christine E. A.; Stock, Norbert; De Vos, Dirk; Ameloot, Rob
Abstract : In water, UTSA-74 transforms through a dissolution–recrystallization process to its polymorph MOF-74(Zn). Abstract : We report the water-induced transformation of the [Zn2 (dobdc)] (dobdc = 2, 5-dioxidobenzene-1, 4-dicarboxylate) metal–organic framework UTSA-74 to its polymorph MOF-74(Zn), contrary to a previous report on the stability of UTSA-74 under such conditions. This dissolution–recrystallization process was investigated using time-resolved in situ X-ray diffraction and kinetically analyzed using the Gualtieri crystallization model.